Učinkovitost celostne obravnave otrok z motnjami hranjenja in s prevladujočo senzorno preobčutljivostjo - Korošec, Barbara (Rehabilitacija (Ljubljana), 2019)
Background: Feeding problems are often associated with hypersensitivity to oral stimuli. Because of difficulties in the development of sensation and tolerance of individual oral stimuli, such children often selectively accept only a particular type or food texture. In 2015, at the Department for Rehabilitation of Children at the University Rehabilitation Institute of the Republic of Slovenia in Ljubljana, an outpatient program for eating disorders was introduced, as well as the sequential oral sensory approach (SOS) therapy program. In this study, we wanted to check which children were referred to our programs, determine their feeding problems, and evaluate the effectiveness of the therapeutic program. We also wanted to check how parents are satisfied with the therapy program. Methods: In this retrospective study, we included 123 children who were referred because of eating disorders to our outpatient program in the period from February to August 2018. We excluded the data of 36 children who were only consulted at the outpatient clinic once. For two children it turned out that feeding was not safe, two halted treatments due to long-term illness, four children had only started the program. We collected data on the child's feeding problems, the number of treatments and the number of foods that children eat at the end of the program. We sent a questionnaire to the parents about their satisfaction with the program and how the children progress in their home environment Results: The survey included data on 79 children (44 boys, 35 girls), with an average age of 2.5 years (SD 2.8). Different syndromes and genetic defects (n = 33), preterm birth (n = 29) and eating disorders with no clear aetiology (n = 25) were the predominant diagnoses. Regarding feeding problems, the children who were selective in their acceptance of food (65 %) dominated, one quarter developed fear of feeding, and a smaller proportion of children did not eat enough. Half of the children were classified in level III V of the Dysphagia Management Staging Scale (DMSS), others had less problems. Of the 14 children who were fed through the percutaneous gastric tube (PEGS) at the beginning, seven of were able to eat orally all the meals at the end of the program. A little less than half of the parents (n = 32) returned the completed questionnaires at the end of the program. They reported that the children have increased the number of foods they eat. In general, the parents were very satisfied with the content of the program. The vast majority of them believed that the progress of the child was most influenced by the deliberate and systematic introduction of new food in the home environment and in the SOS therapy program. Conclusion: The SOS therapy program has proven to be effective. The children in the program significantly increased the number of foods they were willing to eat. In general, the satisfaction of parents was also good; the program made them feel less worried and stressed due to child's feeding problems.
Keywords: child; eating disorders; Feeding and Eating Disorders of Childhood; motnje hranjenja; otrok; rehabilitation; sensory sensitivity; senzorna preobčutljivost; sequential oral sensory approach; stopenjski senzorni pristop; terapija; therapy